Distributional cost effectiveness analysis of West Yorkshire low emission zone policies. (30th January 2020) - Griffin, Susan; Walker, Simon; Sculpher, Mark
Abstract: Alternative strategies can reduce road vehicle emissions, with differential effects on exposure across population groups. We compare alternative strategies in West Yorkshire using a framework for economic evaluation that considers multiple perspectives and that takes account of the distribution of health outcomes. Exposure to pollutants by area is converted, via dose response relationships, into disease averted. Health benefits and National Health Service costs from diseases are estimated conditional on population demographics and index of multiple deprivation. The net health benefits from alternative strategies are expressed as distributions of quality‐adjusted life expectancy (QALE), which are compared using dominance criteria and societal aversion to health inequality. Net production is estimated from intervention costs and the effects of health improvement on production and consumption. Social care outcomes are estimated from health improvement among care recipients and changes in care expenditure. A switch to less polluting private vehicles is dominant in terms of the distribution of QALE and social care outcomes but not consumption. Inclusion of health inequality aversion alters the rank order compared with prioritisation on health maximisation. The results were sensitive to the magnitude of health opportunity costs, the level of inequality aversion, and the proportion of intervention cost that generates health opportunity cost.